1985
DOI: 10.1111/j.1365-2222.1985.tb02298.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell activity in atopic dermatitis: a sequential study

Abstract: Summary It is well‐recognized that patients with atopic dermatitis handle certain cutaneous viral infections poorly. As natural killer (NK) cell activity is considered to contribute to the immune response to viral infection, seven young adults with atopic dermatitis had their NK cell function assessed over a 12‐month period. Natural killer cell activity was found to correlate inversely with disease activity. The more active the disease, the greater was the reduction in NK cell function (P<0.01). In addition, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…These observations confirm recent results of Timonen et al, (20), However, IgE-mediated allergy (initially presented as atopie dermatitis) has been shown to have strongly suppressed NK activity (11,12), These observations suggest that there might be qualitative and/or quantitative differences in these types of allergy in respect to cell-mediated immunity. These observations confirm recent results of Timonen et al, (20), However, IgE-mediated allergy (initially presented as atopie dermatitis) has been shown to have strongly suppressed NK activity (11,12), These observations suggest that there might be qualitative and/or quantitative differences in these types of allergy in respect to cell-mediated immunity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These observations confirm recent results of Timonen et al, (20), However, IgE-mediated allergy (initially presented as atopie dermatitis) has been shown to have strongly suppressed NK activity (11,12), These observations suggest that there might be qualitative and/or quantitative differences in these types of allergy in respect to cell-mediated immunity. These observations confirm recent results of Timonen et al, (20), However, IgE-mediated allergy (initially presented as atopie dermatitis) has been shown to have strongly suppressed NK activity (11,12), These observations suggest that there might be qualitative and/or quantitative differences in these types of allergy in respect to cell-mediated immunity.…”
Section: Discussionsupporting
confidence: 91%
“…Cytotoxicity of LAK cells has been suggested to include allogeneic, autologous tumor cells and hapten-modifled autologous cells (6,16,19). Because of the evident discrepancy of data on NK activity in IgE-mediated allergies in the literature (11,12,20) and the lack of information on LAK activity in this study we investigated these indices. Because of the evident discrepancy of data on NK activity in IgE-mediated allergies in the literature (11,12,20) and the lack of information on LAK activity in this study we investigated these indices.…”
mentioning
confidence: 99%
“…In contrast, Hsieh (1992) found that CD4+ T-lymphocyte numbers were reduced and CD8+ T-lymphocytes increased. Others have reported a reduction in CD8+ cytotoxic cell numbers, as well as decreases in the number and function of natural killer cells (Leung et al 1981;Zachary and MacDonald 1983;Lever et al 1985;Fennerty et al 1988;Kagi et al 1994). The CD4+/CD8+ ratio has also been reported to be significantly higher in allergic than normal individuals during allergen challenge, and a significant correlation between the CD4+/CD8+ ratio and clinical signs has been demonstrated (Leung et al 198 1 ;Fennerty et al 1988;Monteseirin et al 1995).…”
Section: Discussionmentioning
confidence: 96%
“…In addition to cell-mediated defects of the T cell arm, defects in monocyte and neutrophil chemotaxis were observed [16.17] and may be implicated in the enhanced susceptibility of the patients to infections, particularly with Staphylococcus aurcus [1,18]. However, most of these 'abnormalities' normalized during remission of the disease [13,17,19,20]. Therefore, it appears likely that these changes represent epiphenomena of inflammation, rather than signs of immune deficiency.…”
Section: Deficiency Of the Immune System?mentioning
confidence: 99%